Pengembangan Laboratorium Virtual Berbasis Pendidikan Karakter untuk Siswa Sekolah Dasar - Dwiyanti, Aris Naeni; Riwanto, Mawan Akhir; Budiarti, Wahyu Nuning (Universitas Sebelas Maret, 2019)
This study aims to 1) Develop prototype technology in the form of character education based virtual laboratories 2) Know the quality of prototype technology in the form of character education based virtual laboratories. This type of research is research and development research using the Borg & Gall research model which consists of 10 stages. Subjects, populations and samples in this study include teachers, Elementary School Students, Media Specialists, Material Experts, Linguists and Psychologists. The results of this study are 1) The prototype of technology in the form of a virtual laboratory based on character education for class IV 2013 curriculum consists of 1 theme, in 1 the theme consists of 8 experiments 2) The quality of the virtual laboratory according to the assessment of media experts, material experts, linguists, experts psychology, teachers, and students are in the good category.